2019
DOI: 10.1007/s00170-019-03942-5
|View full text |Cite
|
Sign up to set email alerts
|

Current and future Industry 4.0 capabilities for information and knowledge sharing

Abstract: Humans are indispensable in the manufacturing industry as its complexity increases in an Industry 4.0 context, mainly due to changing customer demands. Managing the challenges of increased complexity can create a competitive advantage for SMEs. Technologies which enable the emerging phenomenon of Industry 4.0 have the possibility to simplify the sharing of information and knowledge among people at work, especially for Operator 4.0. However, few SMEs have actually implemented such technologies for this purpose.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 35 publications
1
70
0
1
Order By: Relevance
“…The importance of data and technologies to improve knowledge management within companies and between companies has been assessed through many articles linking them with performance [28], innovation and development [29], or engagement of the workforce [30]. The need for improved and increased knowledge sharing opportunities due to Industry 4.0 development is also a fact, but also, the other way around, Industry 4.0 can increase knowledge-sharing opportunities through the introduction of technologies that more efficiently support information sharing [31].…”
mentioning
confidence: 99%
“…The importance of data and technologies to improve knowledge management within companies and between companies has been assessed through many articles linking them with performance [28], innovation and development [29], or engagement of the workforce [30]. The need for improved and increased knowledge sharing opportunities due to Industry 4.0 development is also a fact, but also, the other way around, Industry 4.0 can increase knowledge-sharing opportunities through the introduction of technologies that more efficiently support information sharing [31].…”
mentioning
confidence: 99%
“…The migration of an SME company to Industry 4.0 depends a lot of states in which the company is located (its cultural organization, its information systems, organizational structure, and resources), which is possible to be known through a survey of the SMEs that helps to collect information to know the status of the company and finally focus on Industry 4.0 [16].…”
Section: Ai (Or Artificialmentioning
confidence: 99%
“…These challenges include poor professional training and a lack of digital culture, a lack of clear vision, high financial requirements for investment, recruitment, and development of new talents, and a general reluctance of all parties involved to change [21][22][23][24]. Industrial enterprises seek to continuously improve in all areas of business and take advantage of opportunities, whether financial or non-financial in their favor [25,26]. The study by [27] identified the impact of industry 4.0 on business performance.…”
Section: Introductionmentioning
confidence: 99%